Efektivitas Pelatihan Mandiri Platform Merdeka Mengajar ( PMM ) terhadap Peningkatan Kompetensi Guru - Supardi U.S.; Rosdiana Rosdiana (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Improving teacher competency is a key factor in improving the quality of education. One of the latest innovations in teacher professional development in Indonesia is the Merdeka Mengajar Platform (PMM), a digital-based platform designed to provide flexible access to independent training. This study aims to evaluate the effectiveness of PMM in improving teachers' pedagogical and professional competencies, especially in the context of educational transformation in the digital era. The method used is a literature study, by collecting and analyzing relevant literature from reputable academic sources. The results of the study indicate that PMM significantly improves teacher competency through interactive modules, online learning communities, and digital resources designed for learning personalization. Teachers who participate in training through PMM show better ability in implementing innovative learning strategies compared to those who do not use this platform or participate in traditional training. However, the effectiveness of PMM can be influenced by teachers' technological readiness and digital literacy, especially in areas with limited infrastructure. This study highlights the importance of supporting technology-based education policies to ensure that the benefits of PMM can be felt inclusively and sustainably. In conclusion, PMM is a promising solution to address the teacher training gap in Indonesia, but requires a strategic approach to improve its access and effectiveness. Further research is needed to evaluate the long-term empirical impact of this platform on teacher professional development and student learning quality.